Estimating shear strength of high-level pillars supported with cemented backfilling using the Hoek–Brown strength criterion - Kaizong Xia; Congxin Chen; Xiumin Liu; Yue Wang; Xuanting Liu; Jiahao Yuan (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
Deep metal mines are often mined using the high-level pillars with subsequent cementation backfilling (HLSCB) mining method. At the design stage, it is therefore important to have a reasonable method for determining the shear strength of the high-level pillars (i.e. cohesion and internal friction angle) when they are supported by cemented backfilling. In this study, a formula was derived for the upper limit of the confining pressure σ3max on a high-level pillar supported by cemented backfilling in a deep metal mine. A new method of estimating the shear strength of such pillars was then proposed based on the Hoek–Brown failure criterion. Our analysis indicates that the horizontal stress σhh acting on the cemented backfill pillar can be simplified by expressing it as a constant value. A reasonable and effective value for σ3max can then be determined. The value of σ3max predicted using the proposed method is generally less than 3 MPa. Within this range, the shear strength of the high-level pillar is accurately calculated using the equivalent Mohr–Coulomb theory. The proposed method can effectively avoid the calculation of inaccurate shear strength values for the high-level pillars when the original Hoek–Brown criterion is used in the presence of large confining pressures, i.e. the situation in which the cohesion value is too large and the friction angle is too small can effectively be avoided. The proposed method is applied to a deep metal mine in China that is being excavated using the HLSCB method. The shear strength parameters of the high-level pillars obtained using the proposed method were input in the numerical simulations. The numerical results show that the recommended level heights and sizes of the high-level pillars and rooms in the mine are rational.